The social context of smoking: A qualitative study comparing smokers of high versus low socioeconomic position - Bonevski Billie; Hill Wesley; Ross Samantha; Bryant Jamie; Paul Christine L; Keevy Nichola (BMC, 2010)
Abstract Background The reductions in smoking prevalence in a number of industrialised countries are accompanied by a strong social gap and associated health inequality. Groups such as the World Health Organisation emphasise the importance of exploring potential causal factors for smoking such as socio-economic context & position. There has been little effort to compare the social context of smoking for smokers of high versus lower socio-economic position (SEP) to consider how tobacco control efforts might reduce smoking-related health inequality. Method Purposive sampling was used to recruit participants for eight focus groups. The groups were segregated by age, gender and SEP. Samples were selected from suburbs within the Sydney metropolitan area defined as either high or low SEP based on the Socio Economic Index for Areas. Emergent themes were analysed according to Poland's six dimensions of the social context of smoking. Differences according to SEP, age group and gender were explored. Results While there was commonality in social experiences for smokers across groups, some important aspects of the social context of smoking varied. Smokers of high SEP appeared to be aware of particular social pressures not to smoke on five of the six social context dimensions (power, body, identity, consumption and place). Not only were some of those pressures absent for low SEP participants, there were additional influences within the social context which were pro-smoking. Conclusions In order to narrow the health inequality gap associated with smoking, it is important to take account of the more pro-smoking social context experienced by low SEP smokers. Suggestions are made regarding social marketing campaigns, support for quit assistance and approaches to the regulation of smoking which may assist in minimising smoking-related health inequality.